Optimisation of CAFE assay for the evaluation of ethanol preference in Drosophila melanogaster - Omar, Jiyan Ali (Zanco Journal of Pure and Applied Sciences, 2022)
Alcohol is one of the most harmful psychoactive drugs which can cause various medical, physical, social, financial, and work-related problems. The fruit fly Drosophila melanogaster has been proposed to be a useful model to explore alcohol-induced behavioural, cellular and molecular mechanisms. The capillary feeder assay (CAFE) has been used to measure the development of preference for alcohol that is observable in Drosophila as well in mammals including humans. The aim of this study was to investigate and optimize the CAFE assay to validate further studies using this technique. The parameters that were investigated were: the ethanol concentration and length of exposure, both during pre-exposure and during the preference assay, and whether the sex of the flies affected the outcome. The results indicate that a minimum of two days of pre-exposure of 15% ethanol is required to induce preference for 15% vs 5% ethanol, while there was no significant difference in extending the preference assay beyond two hours and males and females flies behaved in similar manner. Overall these results further validate and better define the usefulness of the CAFE assay for the measurement of alcohol preference in Drosophila as a method to explore the mechanisms of preference which may apply also to higher organisms.